2008
DOI: 10.1002/pola.22729
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a series of biodegradable and biocompatible PEG‐supported poly(lactic‐ran‐glycolic acid) amphiphilic barbell‐like copolymers

Abstract: A series of multihydroxyl (2, 4, and 8) terminated poly(ethylene glycol)s and their biodegradable, biocompatible, and branched barbell‐like (PLGA)n‐b‐PEG‐b‐(PLGA)n (n = 1, 2, 4) copolymers have been synthesized. The lengths of the PLGA arms were varied by controlling the molar ratio of monomers to hydroxyl groups of PEG ([LA+GA]0/[OH]0 = 23, 45, 90). Chemical structures of synthesized barbell‐like copolymers were confirmed by both 1H and 13C‐NMR spectroscopies. Molecular weights were determined by 1H‐NMR end‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…As shown in Figure 3D, the T g of the 3S-PLGA was about 50.91°C, while 3S-PLGA-PEG was 47.5°C. The results showed that the T g of 3S-PLGA-PEG was lower than 3S-PLGA because the existence of PEG can affect the crystalline property of PLGA, which can reduce the T g of this polymer, 33,34 and suggested the PEG segment was linked with PLGA.…”
Section: Characterization Of Micelles Critical Micelle-concentration mentioning
confidence: 96%
“…As shown in Figure 3D, the T g of the 3S-PLGA was about 50.91°C, while 3S-PLGA-PEG was 47.5°C. The results showed that the T g of 3S-PLGA-PEG was lower than 3S-PLGA because the existence of PEG can affect the crystalline property of PLGA, which can reduce the T g of this polymer, 33,34 and suggested the PEG segment was linked with PLGA.…”
Section: Characterization Of Micelles Critical Micelle-concentration mentioning
confidence: 96%
“…[15] Recently, Lu et al reported PEG-supported poly[(lactic acid)-ran-(glycolic acid)] barbell-like copolymers as novel potential biomaterials, and disclosed that thermal properties depended on the structural variations. [16] Interestingly, asymmetric AB n -shaped copolymers, having a linear polymer chain made of PEG and n poly(L-lactide) arms of 2 kDa molecular weight, have been described by Cao and coworkers, and showed a strong molecular architecture dependence on thermal and crystallization behavior. [17] In this framework, by using a diverse chemical approach, we obtained an extended preparation of analogous ''tree-shaped'' copolymers, having a linear polymer chain (core) made of PEG monomethyl ether, from which not only stereoregular isotactic PLLA branches, but also stereoirregular, atactic PDLLA chains start (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The tetra-hydroxyl MPEG was synthesized as previously (Lu et al, 2008). The procedure was described as follows: A three-neck flask equipped with a magnetic stirring bar was charged with MPEG (20 g, 10 mmol), sodium (2.3 g, 100 mmol) and 60 mL of THF.…”
Section: Synthesis Of Tetra-hydroxyl Mpegmentioning
confidence: 99%